Reliability of Technological Parameters in Road Infrastructure Maintenance - Čovo, Petar; Baričević, Hrvoje; Vukušić, Ante (Promet - Traffic&Transportation, 2012)
It may be well said that the most used indicator of the quality of any technical system is reliability. Basically, this indicator shows the probability of proper technical system functioning within certain time period and under given operating conditions. To ensure that a system under construction possesses adequate given pre-defined characteristics and reliability indicators, it is necessary to plan the reliability and apply suitable methods when new technical systems are developed. Road represents an elementary traffic subsystem, as well as a technical subsystem, constructed by the society in order to meet the communication needs. Its purpose is to enable traffic system functioning. If a road is seen as a system, one can observe the features determining the structure and the principal on which its function is based. The road functioning itself is characterized by a variety of features, the most important being the management characteristic and specific social interest, categorization structure, and roadway condition. To enable smooth and safe traffic, roads should be of prescribed technical and usage levels. Reference is made specifically to road maintenance in the Primorje-Gorski Kotar County.KEYWORDS: infrastructure, terotechnology, road network, maintenance, theory of benefit